The evolution of BDNF is defined by strict purifying selection and prodomain spatial coevolution, but what does it mean for human brain disease? - Alexander G. Lucaci; Michael J. Notaras; Sergei L. Kosakovsky Pond; Dilek Colak (Translational Psychiatry, 2022)
Abstract Brain-Derived Neurotrophic Factor (BDNF) is an essential mediator of brain assembly, development, and maturation. BDNF has been implicated in a variety of brain disorders such as neurodevelopmental disorders (e.g., autism spectrum disorder), neuropsychiatric disorders (e.g., anxiety, depression, PTSD, and schizophrenia), and various neurodegenerative disorders (e.g., Parkinson’s, Alzheimer’s, etc.). To better understand the role of BDNF in disease, we sought to define the evolution of BDNF within Mammalia. We conducted sequence alignment and phylogenetic reconstruction of BDNF across a diverse selection of >160 mammalian species spanning ~177 million years of evolution. The selective evolutionary change was examined via several independent computational models of codon evolution including FEL (pervasive diversifying selection), MEME (episodic selection), and BGM (structural coevolution of sites within a single molecule). We report strict purifying selection in the main functional domain of BDNF (NGF domain, essentially comprising the mature BDNF protein). Additionally, we discover six sites in our homologous alignment which are under episodic selection in early regulatory regions (i.e. the prodomain) and 23 pairs of coevolving sites that are distributed across the entirety of BDNF. Coevolving BDNF sites exhibited complex spatial relationships and geometric features including triangular relations, acyclic graph networks, double-linked sites, and triple-linked sites, although the most notable pattern to emerge was that changes in the mature region of BDNF tended to coevolve along with sites in the prodomain. Thus, we propose that the discovery of both local and distal sites of coevolution likely reflects ‘evolutionary fine-tuning’ of BDNF’s underlying regulation and function in mammals. This tracks with the observation that BDNF’s mature domain (which encodes mature BDNF protein) is largely conserved, while the prodomain (which is linked to regulation and its own unique functionality) exhibits more pervasive and diversifying evolutionary selection. That said, the fact that negative purifying selection also occurs in BDNF’s prodomain also highlights that this region also contains critical sites of sensitivity which also partially explains its disease relevance (via Val66Met and other prodomain variants). Taken together, these computational evolutionary analyses provide important context as to the origins and sensitivity of genetic changes within BDNF that may help to deconvolute the role of BDNF polymorphisms in human brain disorders.